1973
DOI: 10.1159/000162686
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Pneumonitis: Experimental Production in Guinea Pigs with Antigens of <i>Micropolyspora faeni</i>

Abstract: Abstract. Hypersensitivity pneumonitis was produced in guinea pigs by aerosol challenge with antigens of Micropolyspora faeni following systemic immunization with soluble antigens of the organism emulsified in Freund's complete adjuvant. The condition was trans ferred to normal guinea pigs with plasma or washed lymphocytes from immunized animals. The lungs of affected animals had bronchopneumonia with an accom panying interstitial reaction including vasculitis of septal capillaries, proliferation of alveolar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

1975
1975
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…Edwards (1974), by means of intratracheal instillation in immunised rabbits showed that both living cells of M. faeni and glycopeptide antigens extracted from the organism provoked features of both Type I11 and Type IV reactions. These reactions were also implicated by Wilkie, Pauli and Gygax (1973) in guinea-pigs challenged with ultrasonicated cells of M. faeni after previous immunisation with soluble antigens of the organism. Factors initiating the disease were transferred by passive immunisation with plasma or lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Edwards (1974), by means of intratracheal instillation in immunised rabbits showed that both living cells of M. faeni and glycopeptide antigens extracted from the organism provoked features of both Type I11 and Type IV reactions. These reactions were also implicated by Wilkie, Pauli and Gygax (1973) in guinea-pigs challenged with ultrasonicated cells of M. faeni after previous immunisation with soluble antigens of the organism. Factors initiating the disease were transferred by passive immunisation with plasma or lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Unlike calves [16,17] and rabbits [2, 6-8, 12, 15], guinea pigs required systemic as well as pulmonary exposure to M.faeni to become susceptible to an ex aggerated histologic response to an i.t. challenge of M. faeni.…”
Section: Discussionmentioning
confidence: 99%
“…challenge of M. faeni. This difference between guinea pigs and other animals may be due to the frequent occurrence of serum antibodies to M. faeni in calves prior to sen sitization [ 16] or to species differences.…”
Section: Discussionmentioning
confidence: 99%
“…Passive Cutaneous Anaphylaxis (PCA) Positive Serum Calves were sensitized with soluble M. faeni antigen as described by Wilkie et al [1973]. Sera obtained from these animals were tested for reaginic antibody by PCA reaction in calves [Niel sen et al, 1976].…”
Section: Methodsmentioning
confidence: 99%